Petroleum Profits Tax in Nigeria - Ijaiya, Hakeem (NIU Journal of Humanities, 2018)
There is an old proverb, which states that there is nothing as certain as death and taxes. Taxation is generally recognized as an important and established source of revenue for the Government. There is hardly any country today that does not rely or make pretensions to rely on taxation measures not only to provide the much needed revenue for social-economic development but also to reduce the inequalities of wealth in the society. The tax system is therefore one of the most powerful levers available to any government to stimulate and guide its economic and social development. Taxation therefore looms largely in our lives. Petroleum tax is considered as one of the most important sources of revenue for the government in Nigeria because of the widespread use of petroleum products.